The Dilemma of Online Education in Building Student Character - Hafidurrahman, Moh; Arifin, Samsul; Sholehuddin, Ach (Molang: Journal Islamic Education, 2023)
This study explores the integration of character education in online learning and its impact on students’ moral development through a systematic literature review. It analyzes theoretical frameworks, challenges, and strategies from peer-reviewed articles, books, and credible sources to address ethical issues in digital learning environments. The research identifies key challenges, including reduced teacher-student interactions, limited opportunities for moral reflection, and insufficient real-world practice of ethical behaviors. These challenges undermine critical dimensions of character education—moral knowledge, emotional engagement, and moral action—resulting in fragmented moral development. The findings highlight that online education often lacks the depth of interaction necessary for students to observe, reflect on, and practice moral values. However, it also reveals opportunities to leverage technology for character education. Interactive tools, such as moral simulations, value-based applications, and collaborative online projects, can enhance students’ understanding and application of ethical principles. Teachers remain central to this process, serving as moral role models and facilitators of reflective discussions. The study emphasizes the need for teacher training to adapt pedagogical strategies for digital platforms and maintain emotional engagement with students. Furthermore, the research underscores the importance of collaboration between schools, families, and communities to strengthen character education in online contexts. Practical recommendations include developing teacher competencies in technology-based character education, fostering family involvement, and designing educational technologies that promote ethical behavior. This study contributes to the literature by offering a comprehensive framework for integrating moral and character education into online learning, ensuring it remains a priority in the digital age.